Fintech Adoption Drivers for Innovation among SMEs in Pakistan - *Muhammad Ali Qazi; Kashif Bilal; Usman Arshad (Social Science Review Archives, 2025)
The adoption of technology-driven financial services has brought about significant changes in the way customers interact with SMEs, particularly in developing countries such as Pakistan. Therefore, this study is undertaken to examine the drivers of Fintech adoption for innovation among SMEs in Pakistan. It further scrutinizes the mediating effects of perceived ease of use (PEU) and Fintech adoption mediated by perceived usefulness (PU). It also examines the financial literacy significantly mediated with FinTech intention adoption. The target population was Pakistani people who are 18 years of age or older and having a bank account. Survey questionnaire method was employed, and data were collected from 383 bank account holders respectively by using purposive sampling techniques. PLS-SEM was used for statistical analysis. Findings revealed that the perceived ease of use, financial literacy, and trust in driving fintech adoption, particularly among Small and Medium-sized Enterprises (SMEs). The study revealed that user perceptions of ease of use and trust play crucial roles in influencing adoption, while financial literacy and user innovativeness also contribute to the adoption decision, with perceived usefulness acting as a mediator.